(untitled) (Research, Society and Development, 2021)
This paper is the result of a study that aims to reflect on the response of the Neoliberal State to the demands for social policies, and how responsibility is transferred to civil society regarding the provision of actions to enforce social rights. Civil society, in turn, has been organizing and professionalizing to respond to such demand, although punctually and selectively. Faced with this scenario, concerns arise: how has the State taken responsibility for providing public policies in the social area? Are Third Sector institutions able to fully fulfill the function transferred to them? The research was carried out by data survey and study of bibliography in the following areas: Social Policies, Neoliberal State, and Third Sector. This study was essential for analyzing the performance of civil society institutions with social programs on their work fronts. The study reveals that the responsibility of the State in providing social policies is transferred to civil society as a complementary role, but what occurs is the outsourcing of roles, since, for neoliberals, State intervention in social areas must be minimal.